Toward a New Understanding of American Poverty - Mark R. Rank (Washington University Journal of Law & Policy, 2006)
This Essay argues that one of the fundamental reasons the United States currently has the highest poverty rates in the industrialized world is that we have consistently misunderstood the nature and causes of American poverty. Old strategies of addressing poverty have rested upon imagining a world that reflects a preferred set of myths, agendas, and policies; a new approach to poverty reduction must put in place a set of policies that reflects the realities of the world. These policies should be grounded in a new understanding of the nature and meaning of American poverty. This Essay provides the rudimentary details of such a paradigm.
Keywords: Poverty; Social science research; United States; Economic policy